PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN PADA RESTORAN JAMBO KUPI PASAR MINGGU JAKARTA - Nur Siti Rahayu (LPPM Universitas Asa Indonesia, 2017)
This study aims to determine the effect of service quality and product quality on customer satisfaction at Restaurant Jambo Kupi Pasar Minggu Jakarta. The type of data in this study is primary or data derived from respondents who contain opinions of respondents will be dimensions of service quality, product quality, and customer satisfaction. Data collection can be through questionnaire instrument. The population in this study were all consumers of Jambo Kupi Restaurant Pasar Minggu Jakarta with a sample of 100 respondents and randomly distributed (Accidental Sampling). The method of analysis using descriptive and quantitative methods. From the results of research on partial variables, the value of t is greater than t table, then Ha shows and states there is a positive and significant influence between service quality and product quality to customer satisfaction. The percentage of influence on the quality of service and product quality given to consumers Jambo Kupi Pasar Minggu Jakarta amounted to 30,14%, while the rest are still influenced by other variables such as price factors, location factors and others.